Lattice Boltzmann model for predicting the deposition of inertial particles transported by a turbulent flow. (November 2015) - Fede, Pascal; Sofonea, Victor; Fournier, Richard; Blanco, Stéphane; Simonin, Olivier; Lepoutère, Guillaume; Ambruş, Victor
Highlights: We propose new Gauss-Hermite Lattice Boltzmann models for gas–solid turbulent flows. The LBM model solves directly a kinetic equation describing particle laden flows. The deposition of inertial particle is well predicted by the LBM approach. Abstract: Deposition of inertial solid particles transported by turbulent flows is modelled in a framework of a statistical approach based on the particle velocity Probability Density Function (PDF). The particle-turbulence interaction term is closed in the kinetic equation by a model widely inspired from the famous BGK model of the kinetic theory of rarefied gases. A Gauss-Hermite Lattice Boltzmann model is used to solve the closed kinetic equation involving the turbulence effect. The Lattice Boltzmann model is used for the case of the deposition of inertial particles transported by a homogeneous isotropic turbulent flows. Even if the carrier phase is homogeneous and isotropic, the presence of the wall coupled with particle-turbulence interactions leads to inhomogeneous particle distribution and non-equilibrium particle fluctuating motion. Despite these complexities the predictions of the Lattice Boltzmann model are in very good accordance with random-walk simulations. More specifically the mean particle velocity, the r.m.s. particle velocity and the deposition rate are all well predicted by the proposed Lattice Boltzmann model.